Pendampingan Penyusunan Aksi Nyata Pelatihan Mandiri pada Platform Merdeka Mengajar dalam Rangka Meningkatkan Kemampuan dan Keterampilan Guru di Sekolah: Assisting in the Preparation of Real Action for Independent Training on the Merdeka Teaching Platform to Improve the Skills and Abilities of Teachers in Schools - Wahyuni, Rina; Ernawatie, Ernawatie; Berliani, Teti; Nugroho, Piter Joko; Purnomo, Widiharto; Radiafilsan, Christian; Febriyanti, Lilik (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Support for the preparation of concrete actions for independent training in the Merdeka Teaching Platform (PMM) in learning communities aims to improve the skills and competence of educators in designing and implementing effective learning activities. Through this approach, learning communities receive direct support in developing action plans that meet their local needs and educational context. The mentoring process includes technical guidance, collaborative discussion, evaluation and continuous development. It is expected to improve the quality of learning in the community and to strengthen the capacity of educators to make best use of PMM to support innovative and adaptive learning processes. The methodology used in this activity starts with: (1) an initial needs assessment; (2) a workshop to prepare for real action; (3) implementation and evaluation; and (4) continuous development. The outcomes of this PkM activity are: (1) teachers gained knowledge on how to develop real actions that are in line with the conditions of teacher learning in schools; and (2) teachers were able to develop two real action topics that became an agreement in the Work Result Plan (RHK) that had been jointly determined.